HIV drug resistance in children and adolescents on NNRTI-based antiretroviral therapy and subsequent virologic response to dolutegravir-based regimens in Ghana - Adwoa K.A Afrane; Vlad Novitsky; Joel Hague; Kwamena Sagoe; Yakubu Alhassan; Joycelyn Assimeng Dame; Charles Martyn-Dickens; Margaret Lartey; Bamenla Goka; Kwasi Torpey; Rami Kantor; Awewura Kwara (AIDS Research and Therapy)
Abstract HIV drug resistance (HIVDR) was retrospectively characterized among 20 children and adolescents with HIV with virologic failure on non-nucleoside reverse transcriptase inhibitor (NNRTI)-based therapy, and virologic response in those switched to dolutegravir (DTG)-based therapy described. All participants had at least one NNRTI resistance mutation, most commonly K103N (N = 12) and 15 (75%) had nucleoside reverse transcriptase inhibitor (NRTI) resistance mutations, most commonly M184I/V (N = 15). Five (45%) of 11 participants who were switched to DTG-based regimens for a median of 50 months had HIV suppression. Further studies to understand the role of pre-existing HIVDR in the failure of DTG-based regimens are needed.